Exploring the relationship between the environmental factors and creativity of children from primary schools of General Santos City - Barluado, Zeska Mariz C. (2020)
The current educational system that is becoming more exam- oriented, consequently limits the creative thinking of children during their early years. This research was conducted to determine how the school environmental factors of an elementary student, affect one?s creativity. The primary-level education environment is divided mainly into three categories: antecedent conditions, person-centered characteristics, and situation-related characteristics. Antecedent conditions include grade level, sex, and class size. Person-centered characteristics include the personality (extraversion, agreeableness, conscientiousness, emotional stability, and openness to experience) and cognitive style (right hemisphere specialization, left hemisphere specialization, and integrative style). Situation-related characteristics include contextual influences (classroom environment: color, light, ambient sound, temperature, natural elements, flexibility, spatial complexity, building environment: space allocation, building age, and campus environment: site area and floor area ratio) is and social influences that is measured through the creativity fostering teacher behavior. Through determining which environmental factors positively influences creativity, the school architecture may be designed to consider such factors that enables creative development among its users. Results show that six of these environment factors namely space allocation, years in education, ambient sound, building age, color, and light, show significant marginal effect on the creative performance of elementary students. Out of the six, space allocation was found to have the highest probability of improving creative thinking. Given that the major Philippines educational concern include the inadequate learning environment conditions, aiming to provide a greater space allocation for the students may become challenging, as the allocated funds to education remain insufficient to provide for the demands of the growing student population.